Efficient terahertz generation in highly nonlinear organic crystal HMB-TMS - Jian, L. U.; Lee, Seung Heon; Xian, L. I.; Lee, Seung Chul; Han, Jae Hyun; Kown, O. Pil; Nelson, Keith A. (Optics Express, 2018)
We report on generation of strong and broadband terahertz (THz) pulses via collinearly phase-matched optical rectification of near-infrared femtosecond pulses in the organic nonlinear optical HMB-TMS (2-(4-hydroxy-3-methoxystyryl)-3-methylbenzo[d]thiazol-3-ium 2,4,6-trimethylbenzenesulfonate) single crystals which exhibit optimal molecular orientation and large macroscopic optical nonlinearity for efficient THz wave generation. Single-cycle THz pulses with a peak electric field strength of 0.66 MV/cm and a bandwidth from 0.1 to 5.4 THz are achieved from an HMB-TMS crystal with only a 2-mm clear aperture pumped by 1350 nm pulses at moderate fluences. The generated THz energy is about 1 µJ and the corresponding pump-to-THz energy conversion efficiency reaches 0.23%.
Keywords: Broadband terahertz; Near Infrared; Non-linear optical; Optical nonlinearity; Optical rectifications; Organic crystal; Peak electric field; Terahertz generation